1998
DOI: 10.1207/s15327752jpa7002_3
|View full text |Cite
|
Sign up to set email alerts
|

Is the Beck Depression Inventory Reliable Over Time? An Evaluation of Multiple Test-Retest Reliability in a Nonclinical College Student Sample

Abstract: The Beck Depression Inventory (BDI) is one of the most widely used measures of depression. Many studies have examined the reliability and validity of the BDI. However, we found no published studies that considered the stability of the BDI over multiple administrations (i.e., more than 3 trials), such as is common in clinical trials research and during some clinical interventions. The purpose of this study is to examine the multiple test-retest reliability of the BDI in a presumably nonclinical sample. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 3 publications
5
14
0
Order By: Relevance
“…These somewhat weaker correlations between PDSS-C scores with greater time between assessment points is consistent with previous research on the relative instability of scores on other well-established measures such as the Beck Depression Inventory (e.g. Ahava, Ianonne, Grebstien, & Schirling, 1998). In addition, psychometric evaluations of the adult PDSS suggest somewhat weaker test-retest reliability with longer delays between assessment points (3-17 days, r = 0.71, compared with r = 0.81 for consecutive days; see Shear et al, 2001 compared with Houck et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…These somewhat weaker correlations between PDSS-C scores with greater time between assessment points is consistent with previous research on the relative instability of scores on other well-established measures such as the Beck Depression Inventory (e.g. Ahava, Ianonne, Grebstien, & Schirling, 1998). In addition, psychometric evaluations of the adult PDSS suggest somewhat weaker test-retest reliability with longer delays between assessment points (3-17 days, r = 0.71, compared with r = 0.81 for consecutive days; see Shear et al, 2001 compared with Houck et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Shortcomings of the BDI are its high item difficulty, lack of representative norms, and thus doubtful objectivity of interpretation, controversial factorial validity, instability of scores over short time intervals (over the course of 1 day), and poor discriminant validity against anxiety. Advantages of the inventory are its high internal consistency, high content validity, validity in differentiating between depressed and nondepressed subjects, sensitivity to change, and international propagation [52]. Generally a two factor model solution is proposed for the BDI, but only the first (general) factor seems to be stable [53].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that repeated administrations of the Beck Depression Inventory and other negative mood measures (Ahava, Iannone, Grebstein, & Schirling, 1998;Sharpe & Gilbert, 1998) and the IOWA Conners (Pelham & Smith, 2000) result in steady declines. On examination of PANAS scores, this was not the case in this study; however, this phenomenon likely contributed to the low parent IOWA Conners scores.…”
Section: Discussionmentioning
confidence: 99%